ANALISIS KINERJA HIGH PRESSURE HEATER (HPH) TIPE SHELL AND TUBE HEAT EXCHANGER - Devia Gahana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2018)
Heat exchanger is one of the supporting production equipment that move the heat energy from one of fluid to another fluid flow. One example of a heat exchanger in power plant industry is High Pressure Heater (HPH). HPH is high pressure feedwater heater that using hot steam turbine waste product used as heating medium before entering the economizer on boiler to reduce the work of boiler. This research was conducted to determine the effective efficiency of High Pressure Heater at Power Plant Industry. This efficiency determination is based on thermodynamics and heat transfer analysis with Log Mean Temperature Difference (LMTD) method and Number of Transfer Unit (NTU) method. The analysis is to determining the effective heat transfer, overall heat transfer coefficient (U), Effectiveness and the analysis of pressure drop (âˆ†P). The analysis results obtained the efffective heat transfer of 37.013 kW, overall heat transfer coefficient (U) of 502,48, effectiveness of 0,47 and the number of pressure drop of 23.498,06 Pa.